Kontekstualisasi Ilmu Jarh wa Ta'dil dalam Penilaian Kinerja Karyawan di PT Dwisar Multivesta Niagatama - Hidayat, Ia Mufti; Arifin, Tajul (Darul Yasin Al Sys, 2024)
Employee assessment is an important aspect of human resource management that requires a comprehensive approach to measuring their performance and contribution to the company. This article aims to explain the concept of jarh wa ta'dil in the science of hadith and how this concept can be applied in the context of employee assessment in modern management. By integrating the ethical values and justice of jarh wa ta'dil, companies can develop a more holistic and value-based approach to judgment. This research uses qualitative methods with a literature study approach by applying descriptive-analytical methods. The results of the research show that there is a correlation between the principles of jahr wa ta'dil with those of the ideal employee judgment. Principles such as justice, equity, and accuracy jhr wa'dil aligned with the ideals of the employee’s judgement such as objectivity, transparency, and accountability.